PENINGKATAN PENGETAHUAN TENTANG ANEMIA DAN KEPATUHAN MINUM TABLET TAMBAH DARAH DENGAN MELALUI PROMOSI KESEHATAN DAN GERAKAN MINUM TABLET TAMBAH DARAH BERSAMA MELALUI MEDIA GRUP WHATSAPP DI SMPN 1 KARANGREJO - Suryani, Lilis; Wati, Dwi Retno; Sumini, Gempi Tri; Sari, Wahyu Anjas (Karsa Husada Health Institute Garut, 2024)
The prevalence of anemia in teenagers in East Java in 2018 was 50-60%. Anemia can be caused by various things, including iron deficiency, vitamin B12 deficiency, folic acid deficiency, infectious diseases, congenital factors and bleeding. The Indonesian government is intensifying its anemia prevention and management program in adolescent girls and women of childbearing age (WUS) by prioritizing the provision of one blood supplement tablet every week to reduce the prevalence of anemia in adolescent girls and WUS by 2025. This research aims to determine the effectiveness of health promotion and a movement to take blood supplement tablets together through WhatsApp Group media to increase knowledge about anemia and compliance with consuming blood supplement tablets among young women at SMPN 1 Karangrejo. This research is included in pre-experimental research using one group pretest and posttest by carrying out a pretest before giving treatment and then doing a posttest after giving treatment. The sample for this research was 92 young women at SMPN 1 Karangrejo. The research results obtained a p value = 0.000 (? 0.05), so it was concluded that there was a difference in the level of knowledge about anemia and compliance with taking blood supplement tablets between before and after being given health promotion and the movement to take blood supplement tablets together via WhatsApp Group, which means health promotion and the movement to take blood-enhancing tablets together via WhatsApp Group is effective in increasing knowledge about anemia among young women at SMPN 1 Karangrejo